2015
DOI: 10.3233/ifs-141484
|View full text |Cite
|
Sign up to set email alerts
|

TWIN: Personality-based Intelligent Recommender System

Abstract: Abstract. This paper presents the "Tell me What I Need" (TWIN) Personality-based Intelligent Recommender System, the goal of which is to recommend items chosen by like-minded (or "twin") people with similar personality types which we estimate from their writings. In order to produce recommendations it applies the results achieved in the personality from the text recognition research field to Personality-based Recommender System user profile modelling. In this way it creates a bridge between the efforts of auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
(40 reference statements)
0
23
0
5
Order By: Relevance
“…The evaluation measures like precision and recall in classification and information retrieval can be used for testing the performance of SA. To evaluate the SA quality of Watson NLU, the sentiment test data were used from the Center for Machine Learning and Intelligent Systems (CMLIS) at the University of California (Kotzias et al, 2015), NLP at Cornell University (Pang et al, 2002), and TripAdvisor data (Roshchina et al, 2015). The requests were sent to Watson NLU API to evaluate the sentiment output metrics of these test data.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation measures like precision and recall in classification and information retrieval can be used for testing the performance of SA. To evaluate the SA quality of Watson NLU, the sentiment test data were used from the Center for Machine Learning and Intelligent Systems (CMLIS) at the University of California (Kotzias et al, 2015), NLP at Cornell University (Pang et al, 2002), and TripAdvisor data (Roshchina et al, 2015). The requests were sent to Watson NLU API to evaluate the sentiment output metrics of these test data.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, in eBay users are also entitled to write reviews about products, and additionally, they can write comments about purchase and sale transactions, since eBay is an e-commerce site. Trip Advisor dataset was extracted as part of the Twin Persona Research Project [41], while eBay dataset was obtained in September 2015 using crawler techniques. Reputation hr /(hr +nhr ), where hr is the total number of reviews set as helpful by others users at least once, and nhr is the total number of reviews that were not set as helpful at least once A text corpus is compatible with our model if it contains: (i) data about users; (ii) texts written by these users; and (iii) data that characterizes the user's trust.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Combining this approach with a rating-based CF technique, the authors showed signifi-cant improvements over the baseline of considering only ratings data. Finally, in [64] Roshchina presented an approach that extracts five factors profiles by analyzing hotel reviews written by users, and incorporates these profiles into a nearest neighbor algorithm to enhance personalized recommendations.…”
Section: Personality-based Collaborative Filteringmentioning
confidence: 99%
“…Moreover, with respect to previous work, the experimental study presented here has been conducted on much larger datasets composed of "likes", which are positive only evaluations, rather than ratings, in several domains. Specifically, as described in Section 4, our dataset consisted of 159,551 users and 16,303 items in the movie, music and book domains, while in [32,33] the considered data set contains only 111 users, in [51] and [64] it is around 100, and in [72] 52; and all of these data sets contain only a very limited number of items.…”
Section: Personality-based Collaborative Filteringmentioning
confidence: 99%